2022
DOI: 10.1371/journal.pgen.1010538
|View full text |Cite
|
Sign up to set email alerts
|

Identification of C. elegans ASNA-1 domains and tissue requirements that differentially influence platinum sensitivity and growth control

Abstract: ASNA1 plays an essential role in cisplatin chemotherapy response, type 2 diabetes, and heart disease. It is also an important biomarker in the treatment response of many diseases. Biochemically, ASNA1 has two mutually exclusive redox-modulated roles: a tail-anchored protein (TAP) targeting function in the reduced state and a holdase/chaperone function in the oxidized state. Assigning biochemical roles of mammalian ASNA1 to biomedical functions is crucial for successful therapy development. Our previous work sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…It has been shown that C. elegans ASNA-1 and its yeast homolog GET3 can work as ATPase-dependent targeting proteins. However, under the high oxidative stress condition, the proteins undergo an oxidation-dependent conformational change and are converted into an ATPase-independent chaperone ( Raj et al, 2021 , 2022 ; Voth et al, 2014 ).…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that C. elegans ASNA-1 and its yeast homolog GET3 can work as ATPase-dependent targeting proteins. However, under the high oxidative stress condition, the proteins undergo an oxidation-dependent conformational change and are converted into an ATPase-independent chaperone ( Raj et al, 2021 , 2022 ; Voth et al, 2014 ).…”
Section: Resultsmentioning
confidence: 99%
“…Our previous work has demonstrated in worms that there is an increase in ROS levels when C. elegans 1-day-old adults are subjected to cisplatin treatment. This consequently led to higher levels of oxidized ASNA-1 and disturbances in ER-targeted tail-anchored membrane protein insertion 9 , 51 . In this study, we started by asking to what extent ROS detoxification was essential for survival.…”
Section: Discussionmentioning
confidence: 99%